Kepuasan Konsumen Terhadap Pembelian Salad Buah Melalui Jasa Layanan Go Food, Grab Food Dan Shopee Food (Studi Kasus : Umkm Nayo Salad) - Putri Seroja ZR; Rahma Sari Siregar; Khairul Saleh (Universitas Medan Area, 2023)
Satisfaction is an assessment of a product by comparing the reality and expectations of food delivery services. Food delivery services are one of the strategic solutions nowadays and promise benefits for culinary business people. One form of business that uses various fruits as the main raw material for its business is fruit salad. Nayo Salad is a Small and Medium Enterprises. located on Jl. Rahmadsyah Gg. Emse No.3 Medan Area District, Medan City Regency. marketing of Nayo fruit salad is marketed offline and online in partnership with Food delivery services in Gofood, Grab Food and Shopee Food services. This study aims to determine Consumer Satisfaction with Purchasing Nayo Fruit Salad through Go-Food, Grab Food and Shopee Food Services. Determining the location of this research was carried out using a purposive method (intentionally). The data analysis method uses the analysis of the Customer Satisfaction Index (CSI) with a qualitative descriptive approach. The results obtained from this study are the percentage of satisfaction levels for nayo salad consumers who buy through Gofood, Grab Food, and Shopee Food services based on the indicators studied, namely service quality, product quality, delivery speed, and distribution options for Nayo fruit salad products